Tourism as a direction of social and economic development of a rural settlement (on the example of "timiryazevsky rural settlement" of the Republic of Adygea) - S. I. Labintseva; N. N. Galinskaya (Новые технологии, 2018)
Every year the share of tourist services in the volume of services consumed by the population becomes more significant. At the same time, the nature of demand in the tourist market is also changing, which determines the need to search for new types of tourist products and discover new directions of tourist flows. The countryside can be considered as a huge and vacant market today.In this regard, the issue of developing investment passports for the development of rural settlements and the economic assessment of tourist resources and the creation of an exclusive tourist product for the formation of an attractive tourist image of the Republic of Adygea becomes topical. This article proposes ways to optimize the use of tourist potential to revive the economy of the depressed territory of Timiryazevskoe Rural Settlement of the Republic, and to form it as a tourist destination.